On the same page: Co-designing the logic model of a telehealth service for children in rural and remote Australia. (January 2019) - Abimbola, Seye; Li, Clare; Mitchell, Michelle; Everett, Michael; Casburn, Kim; Crooks, Philippa; Hammond, Rebecca; Milling, Holly; Ling, Lydia; Reilly, Alexandra; Crawford, Alexandra; Cane, Lindsay; et al.
The value of programme logic models as a tool for planning, evaluation, and communication is well recognised. However, the value of its development process is less discussed. In this paper, we describe how we used a combination of literature review and organisational stakeholder consultations to develop a logic model for a telehealth programme for children in rural and remote Australia. Our aim was to use this process to further embed the programme within its implementing organisation, and by so doing to promote its sustainability and scale-up; a major challenge of telehealth programmes, especially those involving reorganisation of processes. Our efforts to describe the components of this complex intervention on the one-page logic model allowed for debates and discussions within the implementing organisation which then facilitated an improved cross-organisational understanding of the telehealth programme; a real time face-to-face (video-link) service which requires the reorganisation of existing service delivery platforms. The process helped to embed the telehealth programme within existing services. We conclude that stakeholder engagement in developing logic models can transform them from being only a tool that provides the picture of why and how a programme works, to one that plays a role in embedding programmes within implementing organisations.